2023
DOI: 10.1038/s41419-023-05653-y
|View full text |Cite
|
Sign up to set email alerts
|

DNALI1 deficiency causes male infertility with severe asthenozoospermia in humans and mice by disrupting the assembly of the flagellar inner dynein arms and fibrous sheath

Abstract: The axonemal dynein arms (outer (ODA) and inner dynein arms (IDAs)) are multiprotein structures organized by light, intermediate, light intermediate (LIC), and heavy chain proteins. They hydrolyze ATP to promote ciliary and flagellar movement. Till now, a variety of dynein protein deficiencies have been linked with asthenospermia (ASZ), highlighting the significance of these structures in human sperm motility. Herein, we detected bi-allelic DNALI1 mutations [c.663_666del (p.Glu221fs)], in an ASZ patient, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…Therefore, AXDND1 may play dual roles in dynein complexes to accomplish axoneme-mediated cell motility and for cytoplasmic dynein-mediated transport. A similar hypothesis has been raised for the light intermediate dynein chain DNALI1 (32). A variant encoding hypomorphic DNALI1 in mice resulted in axoneme microtubule doublet and fibrous sheath abnormalities (32).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, AXDND1 may play dual roles in dynein complexes to accomplish axoneme-mediated cell motility and for cytoplasmic dynein-mediated transport. A similar hypothesis has been raised for the light intermediate dynein chain DNALI1 (32). A variant encoding hypomorphic DNALI1 in mice resulted in axoneme microtubule doublet and fibrous sheath abnormalities (32).…”
Section: Discussionsupporting
confidence: 68%
“…A similar hypothesis has been raised for the light intermediate dynein chain DNALI1 (32). A variant encoding hypomorphic DNALI1 in mice resulted in axoneme microtubule doublet and fibrous sheath abnormalities (32). Alternatively, the motility defect observed in sperm from Axdnd1 -/- males may be exclusively due to the severe ultrastructural defects, including the partial loss of microtubule doublets and outer dense fibres throughout the axoneme.…”
Section: Discussionsupporting
confidence: 68%
“…As previously reported, DNAH1 deficiency impaired the structure of IDAs and induced morphological abnormalities of spermatozoa in infertile humans and mice 9,12 . To explore the effect of DNAH1 variants on the molecular characteristics of spermatozoa, immunofluorescence assays with antibodies against DNAH1, DNALI1 (a light intermediate chain protein of IDA), 36 DNAI1 (an intermediate chain protein of ODA), 37 and α‐TUBULIN (the main component of microtubules) were performed. The results showed that biallelic DNAH1 variants induced the absence of DNAH1 and a decrease in α‐TUBULIN in the spermatozoa of males with MMAF (Figure 4A).…”
Section: Resultsmentioning
confidence: 97%
“…For instance, Dna14, which encodes Dynein axonemal intermediate zoa motility and ciliary transport of the oocyte in the oviduct and fallopian tube is the most relevant. 41,42 As the specific function of DNAI4 has not yet been described in this respect, future investigations may wish to elucidate the role of this specific dynein in in vitro or in vivo models. The other uncharacterized protein in the high-fertility sEV group, A5PKB9 (C16orf54) has been implicated as a potential diagnostic/prognostic in Pancancer, 43 and in lipid droplet formation, 44 thus its association with reproductive status is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, each high- and low-fertility protein biomarker group contained two proteins that have not been previously classified as vesicular in origin in the online EV database Vesiclepedia and may represent a novel finding. For instance, Dna14 , which encodes Dynein axonemal intermediate chain 4 (DNAI4), was exclusively detected in high-fertility sEV samples and has not been well-characterized; however, other members of the dynein complex family have been under study for their roles in vertebrate male and female infertility, namely dynein axenomal intermediate and light chains DNAI1 and DNAL1. The dynein family of motor proteins perform a wide range of biological functions, but in the context of reproduction and reproductive deficits, their role in spermatozoa motility and ciliary transport of the oocyte in the oviduct and fallopian tube is the most relevant. , As the specific function of DNAI4 has not yet been described in this respect, future investigations may wish to elucidate the role of this specific dynein in in vitro or in vivo models. The other uncharacterized protein in the high-fertility sEV group, A5PKB9 ( C16orf54 ) has been implicated as a potential diagnostic/prognostic in Pan-cancer, and in lipid droplet formation, thus its association with reproductive status is unclear.…”
Section: Discussionmentioning
confidence: 99%